Sistematization and differentiation of hospital infections on epidemiological and clinical signs - A. A. Kuzin; P. I. Ogarkov; I. M. Samokhvalov (Журнал инфектологии)
In the review the analysis of data on hospital infections which can be used at the organization of their prophylaxis in the hospitals. Systematization and differentiation of hospital infections depending on the reasons and conditions of occurrence, mechanisms of development, clinical and epidemiological signs has great value. It will assist specialists in planning and carrying out of the measures directed on improvement of quality of treatment of patients and increase of epidemiological safety of the hospital environment.